2018
DOI: 10.1111/mmi.14105
|View full text |Cite
|
Sign up to set email alerts
|

ATP reduction by MgtC and Mg2+ homeostasis by MgtA and MgtB enables Salmonella to accumulate RpoS upon low cytoplasmic Mg2+ stress

Abstract: RpoS is one of several alternative sigma factors known to alter gene expression profiles by RpoS-associated RNA polymerase in response to a variety of stresses. The enteric bacteria Salmonella enterica and Escherichia coli accumulate RpoS under low Mg concentrations via a common mechanism in which the PhoP regulator activates expression of antiadaptor proteins that, by sequestering the adaptor RssB, prevent RpoS degradation by the protease ClpXP. Here, we demonstrate that this genetic program alone does not fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
14
0
1
Order By: Relevance
“…As a result, in order to better understand the virulence mechanism of pathogens, many studies were devoted to elucidating key genes related to stress resistance (Gupta et al, 2019;Tian et al, 2008). Among these, RpoS was proved to enable transcription of genes associated with the general stress response and stationary phase metabolism (Campos-Gomez & Benitez, 2018;Park, Nam, Kweon, & Shin, 2018). Meanwhile, rpoS was closely related to the virulence regulation of pathogenic bacteria (Xiao et al, 2009;Yin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, in order to better understand the virulence mechanism of pathogens, many studies were devoted to elucidating key genes related to stress resistance (Gupta et al, 2019;Tian et al, 2008). Among these, RpoS was proved to enable transcription of genes associated with the general stress response and stationary phase metabolism (Campos-Gomez & Benitez, 2018;Park, Nam, Kweon, & Shin, 2018). Meanwhile, rpoS was closely related to the virulence regulation of pathogenic bacteria (Xiao et al, 2009;Yin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…RpoS combines with RNA polymerase (RNAP) to regulate many genes by binding to gene promotors and initiating transcription that enables bacteria to survive adverse conditions (37,38). Research also showed that missense mutants in RpoS can affect its function including interacting with RNAP in E. coli (STEC) isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a Salmonella mgtC atpB double mutant strain-containing a genetically inactive ATP synthase-was also reported to harbor lower ATP levels than an mgtC single mutant strain during cytoplasmic Mg 2+ starvation (30). This result led to the notion that MgtC also prevents a non-physiological rise in ATP levels by inhibiting the F 1 F O ATP synthase when Salmonella experiences cytoplasmic Mg 2+ starvation (30,39,40). However, because the biochemical function of MgtC during cytoplasmic Mg 2+ starvation can be genetically separated from its function during intramacrophage replication (32), we sought to reexamine the interpretation of the aforementioned experimental results.…”
Section: An F 1 F O Synthase-independent Mechanism Limits Atp Accumulmentioning
confidence: 99%